A preparation method of a doped and modified single crystal manganese-based lithium ion sieve and its application in lithium extraction from salt lakes

By doping modified single-crystal manganese-based lithium ion sieve and adjusting its lattice structure, the problem of poor circulation stability of manganese-based materials during lithium extraction in the salt lake is solved, and higher circulation stability and lithium ion selection are achieved. sex.

CN118343843BActive Publication Date: 2025-02-18SUN YAT SEN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410451735.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-16
Publication Date
2025-02-18
Estimated Expiration
2044-04-16

AI Technical Summary

Technical Problem

The existing manganese-based materials have poor circulation stability during lithium extraction in the salt lake, and are prone to problems such as manganese dissolution and Jahn-Teller effect.

Method used

By doping modified single-crystal manganese-based lithium ion sieve, cation doping elements such as Al, Ni, Cr, Cu, etc., adjust the lattice structure and reduce the proportion of manganese elements, thereby improving the cyclic stability of the material.

Benefits of technology

Doped modified single-crystal manganese-based lithium ion sieve significantly improves cyclic stability during the lithium extraction process of salt lakes, reduces the influence of manganese dissolution loss and Jahn-Teller effect, and enhances the capacity and ion selectivity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118343843B_ABST
    Figure CN118343843B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a doped and modified single crystal manganese-based lithium ion sieve and its application in extracting lithium from salt lakes. 2‑x M x O4, 0≤x≤0.1, M includes at least one of Al, Ni, Cr, and Cu; the doped and modified single crystal manganese-based lithium ion sieve is a spinel crystal. In the doped and modified single crystal manganese-based lithium ion sieve of the present invention, cation doping reduces the crystal lattice on the one hand, and cation doping replaces part of the manganese element on the other hand, reducing the proportion of manganese element, reducing the manganese dissolution loss caused by the disproportionation reaction, and alleviating the Jahn-Teller effect of the crystal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of salt lake lithium extraction materials, and in particular to a preparation method of a doped and modified single crystal manganese-based lithium ion sieve and its application in salt lake lithium extraction. Background Art

[0002] At present, the rapid development of the electric vehicle field has also stimulated the consumption of upstream lithium resources, so it is necessary to increase lithium production to cope with the shortage of lithium resources.

[0003] The main source of lithium resources is still solid lithium resources such as ores, while liquid lithium resources such as salt lakes, which have more abundant reserves, have not been well developed. Electrochemical lithium extraction has the advantages of being green and environmentally friendly, high lithium extraction efficiency and low lithium extraction cost. If it can be applied to the development of liquid lithium resources, it can solve the shortage of lithium resources and provide strong raw material support for the electric vehicle manufacturing industry.

[0004] Manganese-based materials have attracted much attention due to their unique large specific capacity, which means that manganese-based ion sieves have a higher adsorption capacity in lithium extraction from salt lakes. However, manganese-based materials also face problems such as manganese dissolution and Jahn-Teller effect, resulting in poor cycle stability. Therefore, it is necessary to improve their cycle performance based on manganese-based materials.

[0005] In addition, single crystal ion sieves have broad prospects in the application of electrochemical lithium extraction. First, single crystals have a highly ordered crystal structure, and compared with polycrystalline materials, they have fewer defects at grain boundaries and within the crystal, which enables single crystals to better maintain their shape and structural integrity during the electrochemical process, and can effectively alleviate the problems caused by manganese dissolution and Jahn-Teller effect. Secondly, the lattice structure of single crystal materials has better ion conductivity, which can carry out lithium ion insertion and deinsertion reactions more quickly, help reduce electrode contact resistance, and improve interfacial charge conduction efficiency. Thirdly, the surface of single crystal ion sieves usually has more active sites, which can provide more lithium insertion / deinsertion reaction sites, and at the same time are beneficial to the transport of ions in the active electrode. Summary of the invention

[0006] In order to solve the problem of poor cycle stability of the above-mentioned existing manganese-based materials, the present invention provides a doped modified single crystal manganese-based lithium ion sieve. On the one hand, cation doping reduces the crystal lattice. For example, the lattice constant of LAMO doped with Al element is The undoped LiMn2O4 is This is due to Al 3+ The ionic radius is Less than Mn 3+ Ionic radius This makes the ions more tightly bound and the structure more stable.2+ The ionic radius is is larger than the ionic radius of Mn, but Cu 2+ After ion doping, the lattice constant will decrease, because the Cu-O bond is stronger than the Mn-O bond. On the other hand, the doping of cations will replace part of the manganese element, reducing the proportion of manganese, reducing the manganese dissolution caused by the disproportionation reaction and alleviating the Jahn-Teller effect of the crystal.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a doped and modified single crystal manganese-based lithium ion sieve, wherein the molecular formula of the doped and modified single crystal manganese-based lithium ion sieve is LiMn 2-x M x O4, 0≤x≤0.1, M includes at least one of Al, Ni, Cr, and Cu; the doped and modified single crystal manganese-based lithium ion sieve is a spinel crystal type.

[0009] The second aspect of the present invention provides a method for preparing the doped modified single crystal manganese-based lithium ion sieve, comprising the following steps:

[0010] (1) mixing and dissolving a manganese salt, a surfactant and deionized water to obtain a solution A; dissolving an oxidant in deionized water to obtain a solution B; mixing the solution A and the solution B and transferring them to a hydrothermal reactor for a hydrothermal reaction; washing and drying the hydrothermal reaction product to obtain β-MnO2;

[0011] (2) The β-MnO2, lithium salt and metal compound are mixed in proportion and then calcined to obtain LiMn 2-x M x O4; the metal compound is a mixture of one or more of aluminum salt, nickel salt, chromium salt and copper salt.

[0012] Preferably, in step (1), the manganese salt includes manganese sulfate monohydrate; the surfactant includes polyvinyl pyrrolidone; the oxidant includes sodium chlorate; and further preferably, the surfactant is PVP (30K).

[0013] Preferably, in step (1), the molar ratio of the manganese salt, the surfactant and the oxidant is (0.4-0.6):(0.5-0.6):1.

[0014] Preferably, in step (1), the temperature of the hydrothermal reaction is 140-180°C, and the reaction time is 8-12 hours; further preferably, in step (1), the temperature of the hydrothermal reaction is 150-170°C, and the reaction time is 9-11 hours.

[0015] Preferably, in step (1), the drying temperature is 50-70°C and the time is 10-14 hours; further preferably, in step (1), the drying temperature is 55-65°C and the time is 11-13 hours.

[0016] Preferably, in step (2), the calcination temperature is increased at a rate of 2-4°C / min to 700-900°C, kept at that temperature for 10-12h, and then cooled at a rate of 2-4°C / min; more preferably, the calcination temperature is 750-850°C.

[0017] Preferably, in step (2), the lithium salt is one of lithium hydroxide, lithium carbonate and lithium nitrate; the aluminum salt is aluminum nitrate; the nickel salt is nickel nitrate; the chromium salt is chromium nitrate; and the copper salt is copper nitrate.

[0018] The third aspect of the present invention provides the use of the doped modified single crystal manganese-based lithium ion sieve or the doped modified single crystal manganese-based lithium ion sieve prepared by the preparation method in lithium extraction from salt lakes, wherein lithium is extracted from salt lakes by an electrochemical method, and the doped modified single crystal manganese-based lithium ion sieve is used as a positive electrode load material.

[0019] Preferably, the doped modified single crystal manganese-based lithium ion sieve, polyvinylidene fluoride and conductive carbon black are dissolved in a solvent in a mass ratio of (7.5-8.5): (0.9-1.1):1 and ground to obtain a slurry, and the slurry is coated on conductive carbon paper to obtain the positive electrode.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention prepares single crystal rod-shaped α-MnO2 and single crystal tubular morphology β-MnO2 as precursors. Then the lithium salt, MnO2 precursor and metal compound are mixed in proportion, and finally the mixture is pressed into a sheet and heated at 700°C-900°C for 10 hours to obtain a lithium-intercalated compound. By comparing the lithium-intercalated compounds obtained after the reaction of different precursors, it is found that under the experimental conditions of the present invention, only β-MnO2 as a precursor can prepare a manganese-based electrode material with a single crystal structure. Therefore, the present invention synthesizes LiMn with a high aspect ratio structure from a β-MnO2 precursor. 2-x M x The doped electrode material in the present invention is a single spinel phase material, which has good capacity and ion selectivity, and has improved cycle stability relative to undoped LiMn2O4 material.

[0022] In the material preparation process, the present invention first synthesizes the precursor β-MnO2, and controls the morphology of the precursor to be a hollow tubular morphology through a self-sacrificial template method. After calcination, a structure with a high aspect ratio can be formed, which is beneficial for the contact between the electrode material and the electrolyte and facilitates the insertion and removal of lithium ions. Compared with the adsorption method, the electrochemical method does not require a large amount of acid to wash the lithium ions in the deionized sieve, but instead achieves the deintercalation of lithium ions by reversing the voltage. Therefore, this method is green, efficient, and energy-saving. Compared with the undoped LiMn2O4 electrode, the cation-doped electrode material prepared by the calcination method has a smaller lattice parameter and a more stable structure, which is beneficial to improving the cycle stability performance. The material prepared by the present invention is a single crystal, without the generation of impurities, and the raw materials are successfully converted into lithium-intercalated compounds, with a high raw material utilization rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The XRD diagrams of the α-MnO2 precursor in Comparative Example 2 and the β-MnO2 precursor in Example 1, wherein the X-ray diffractometer scans the entire diffraction area at an angle of 2θ;

[0024] Figure 2 XRD diagrams of the LMO electrode material in Comparative Example 1 and the Al-doped LAMO electrode material in Example 1, wherein the X-ray diffractometer scans the entire diffraction area at an angle of 2θ; the defective type represents LMO, and the modified type represents LAMO;

[0025] Figure 3 XRD and SEM images of the lithium-intercalated compound prepared using α-MnO2 as a precursor in Comparative Example 2, wherein the X-ray diffractometer scans the entire diffraction area at an angle of 2θ;

[0026] Figure 4 The SEM images of the α-MnO2 precursor in Comparative Example 2 (Figure A) and the β-MnO2 precursor in Example 1 (Figure B);

[0027] Figure 5 The SEM images of the LMO electrode material in Comparative Example 1 (Figure A) and the Al-doped LAMO electrode material in Example 1 (Figure B);

[0028] Figure 6 TEM morphology and diffraction spot images of precursors α-MnO2 (Figure A) and β-MnO2 (Figure B);

[0029] Figure 7 TEM morphology, high-resolution image and diffraction spot image of the LMO electrode material in Comparative Example 1 (Figure A) and the Al-doped LAMO electrode material in Example 1 (Figure B);

[0030] Figure 8CV curves of the LMO electrode material in Comparative Example 1 and the Al-doped LAMO electrode material in Example 1 at a scanning rate from 0.05 mV / s to 2 mV / s; the defective type represents LMO, and the modified type represents LAMO;

[0031] Fig. 9 It is a cycle capacity curve of the LMO electrode material in Comparative Example 1 and the Al-doped LAMO electrode material in Example 1 in the voltage range of 0.2V-1.2V under the test conditions of 100mA / g current density and 1M LiCl electrolyte; the defective type represents LMO, and the modified type represents LAMO;

[0032] Fig.10 CV curves of the LMO electrode material in Comparative Example 1 and the Al-doped LAMO electrode material in Example 1 in 1M LiCl, 1M MgCl and 1M LiCl+1M MgCl solutions at a scan rate of 0.5 mV / s; the defective type represents LMO, and the modified type represents LAMO;

[0033] Fig.11 It is a capacity retention curve of the LMO electrode material in Comparative Example 1 and the Al-doped LAMO electrode material in Example 1 under the test conditions of 100 mA / g current density and 1M LiCl electrolyte; the defective type represents LMO, and the modified type represents LAMO;

[0034] Fig.12 It is a graph of manganese dissolution rate of the LMO electrode material in Comparative Example 1 and the Al-doped LAMO electrode material in Example 1 after 100 cycles in the voltage range of 0.2V-1.2V under the test conditions of 100mA / g current density and 1M LiCl electrolyte; the defective type represents LMO, and the modified type represents LAMO. DETAILED DESCRIPTION

[0035] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0036] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0037] Example 1

[0038] This embodiment provides a method for preparing a doped and modified manganese-based electrode material (taking Al doping as an example), comprising the following steps:

[0039] (1) Prepare 50 mL of a mixed solution of 0.4 M manganese sulfate and 0.45 M PVP (30K), prepare 40 mL of a 1 M sodium chlorate solution, mix the above solutions evenly and transfer 70 mL to a 100 mL hydrothermal autoclave, keep warm at 160 ° C for 10 h, filter and wash away excess reactants with distilled water and ethanol to obtain the precursor β-MnO2.

[0040] (2) LiOH, β-MnO2 and Al(NO3)3·9H2O were uniformly mixed in a molar ratio of Li:Mn:Al = 1:1.9:0.1, and then kept at 700°C for 10 hours to obtain LAMO.

[0041] Comparative Example 1

[0042] This comparative example provides a method for preparing an undoped manganese-based electrode material (LMO), referring to Example 1, except that step (2) is to uniformly mix LiOH and β-MnO2 at a molar ratio of Li:Mn=1:2, and then heat at 700°C for 10 hours to obtain LMO.

[0043] Preparation of positive electrode materials: LAMO / LMO: polyvinylidene fluoride (PVDF): conductive carbon black were weighed in a mass ratio of 8:1:1, transferred to an agate mortar, added with an appropriate amount of NMP, and fully ground and mixed to obtain a slurry. The slurry was coated on conductive carbon paper and dried at 60°C for 12 h to obtain a positive electrode.

[0044] Preparation of negative electrode material: activated carbon (AC): polyvinylidene fluoride (PVDF): conductive carbon black were weighed in a mass ratio of 8:1:1, transferred to an agate mortar, added with an appropriate amount of NMP, and thoroughly ground and mixed to obtain a slurry. The slurry was coated on conductive carbon paper and dried at 60°C for 12 h to obtain a negative electrode.

[0045] Comparative Example 2

[0046] This comparative example provides a method for preparing an undoped manganese-based electrode material, comprising the following steps:

[0047] (1) Dissolve oxalic acid as a reducing agent in deionized water to prepare 100 mL of 0.15 M oxalic acid solution D; dissolve potassium permanganate as an oxidizing agent in deionized water to prepare 100 mL of 0.1 M potassium permanganate solution E.

[0048] (2) Solution D was transferred to a beaker, and solution E was transferred to a separatory funnel. Solution E was then continuously dripped into solution D at a rate of 1 mL / min under stirring. The resulting brown solution was stirred at 600°C for 30 minutes to allow it to react fully. The precipitate obtained from the reaction was washed and dried at 120°C for 6 hours.

[0049] (3) The precipitate obtained in step (2) was transferred to a quartz dish and sintered at 600°C for 4 hours to obtain rod-shaped α-MnO2.

[0050] (4) LiOH and α-MnO2 were uniformly mixed in a molar ratio of Li:Mn=1:2, and then kept at 700°C for 10 hours to obtain a lithium-intercalated compound.

[0051] Electrochemical testing

[0052] (1) CV test: The CV test uses a three-electrode test system consisting of a LAMO / LMO electrode as the working electrode, a platinum electrode as the counter electrode, and a saturated calomel electrode as the reference electrode. The electrode liquid is 1M LiCl solution, the voltage range is 0.2V-1.2V, and the scanning rates are 0.05mV / s, 0.1mV / s, 0.2mV / s, 0.5mV / s, 1mV / s, and 2mV / s, respectively.

[0053] (2) Electrochemical cycle test: The electrochemical cycle test was conducted in an H-cell with LAMO / LMO as the positive electrode and activated carbon electrode as the negative electrode. The electrode solution was 1M LiCl solution and the voltage range was 0.2V-1.2V.

[0054] (3) Lithium selectivity test: The lithium selectivity test was conducted using a three-electrode test system consisting of a LAMO / LMO electrode as the working electrode, a platinum electrode as the counter electrode, and a saturated calomel electrode as the reference electrode. The lithium selectivity of the working electrode was tested under the above-mentioned conditions of using 1M LiCl / 1M MgCl2 / 1MLiCl+1M MgCl2 solutions as the electrolyte, with a voltage range of 0.2V-1.2V and a scan rate of 0.5mV / s.

[0055] In the present invention, single crystal rod-shaped manganese-based electrode materials are prepared from two precursors with high aspect ratios, α-MnO2 and β-MnO2. Figure 1 The XRD patterns of α-MnO2 and β-MnO2 precursors correspond to the 44-0141 and 24-0735 standard cards respectively. Compared with the standard spectra, all the diffraction peaks are characteristic peaks, and no impurity peaks are generated. Figure 6In the diffraction spot diagram, it can be seen that both α-MnO2 and β-MnO2 precursors have only one set of diffraction spots, which proves that the prepared precursor MnO2 materials are all single crystal materials, and Figure 4 SEM morphology and Figure 6 From the TEM morphology, we can see that their morphologies are all rod-shaped or tubular. The radius of α-MnO2 is smaller, about 30-40nm, while the outer diameter of β-MnO2 is about 400nm and the inner diameter is about 175nm. Based on the precursor single crystal with a high aspect ratio, the precursor is lithiated, and the XRD of different MnO2 precursors after lithiation is obtained. Figure 2 and Figure 3 , Figure 3 The lithium-intercalated compound obtained by using α-MnO2 as a precursor has a rod-like morphology and its crystal structure is not a pure spinel phase LMO. Figure 2 The LMO prepared from β-MnO2 as a precursor has a spinel single crystal structure. Single crystal materials have high mechanical strength and structural stability, and therefore have better cycle stability, but LMO still has problems such as manganese dissolution in the disproportionation reaction and the Jahn-Teller effect. Therefore, further modification is required on the basis of LMO to obtain better performance. Based on this, the present invention prepares undoped defective materials and doped modified materials (taking Al as an example in the present invention). Figure 2 The XRD of undoped electrode material and doped electrode material is compared in the figure. It can be seen that after Al doping, the sample maintains the spinel phase. The difference is that the peak angle is larger than that of LMO. The lattice constants of the doped and undoped samples are obtained by structure refinement using the Rietveld method. and This indicates that the crystal structure shrinks after Al doping, making the interatomic forces stronger and the crystal structure more stable. Figure 7 The TEM images show that both defective and modified materials have rod-like structures, the atoms in the lattice fringes are arranged regularly, and the diffraction spots are single crystal diffraction, which proves that the materials we prepared are all single crystal structures. The difference is that the modified material is doped with Al. The performance change caused by doping in the cycle stability of lithium extraction can be seen in Fig. 9 , Fig.11 As can be seen from the graph, the defective type has a larger capacity at the beginning, but after 20 cycles, the capacity decays to a lower level than that of the modified electrode material, indicating that doping can improve the cycle performance of the material. Under the same charge and discharge conditions, the capacity retention rate of the modified electrode material is higher, and Fig.12 It can be seen from the Mn dissolution rate that the manganese dissolution rate of the modified electrode material is reduced by 34.2% compared with the unmodified electrode material, which proves that ion doping has a significant effect on inhibiting Mn dissolution and alleviating the Jahn-Teller effect.

[0056] In summary, the present invention provides a method for preparing a doped and modified single crystal manganese-based lithium ion sieve and its application in lithium extraction from salt lakes. The prepared sample presents a complete single crystal structure and a rod-like morphology. The LAMO in Example 1 has better cycle performance than the LMO material in Comparative Example 1. 2+ The excellent lithium ion selectivity in simulated brine content proves the feasibility of the present invention.

[0057] The above examples are only preferred specific implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any relevant personnel familiar with the technical field can replace, change or extend the technical solutions and inventive concepts of the present invention within the technical scope of the present invention, which are all within the protection scope of the present invention.

Claims

1. Application of a doped and modified single crystal manganese-based lithium ion sieve in lithium extraction from salt lakes, characterized in that: The invention discloses an electrochemical method for extracting lithium from a salt lake, and uses the doped and modified single crystal manganese-based lithium ion sieve as a positive electrode load material; the doped and modified single crystal manganese-based lithium ion sieve, polyvinylidene fluoride and conductive carbon black are dissolved in a solvent in a mass ratio of (7.5-8.5): (0.9-1.1): 1, and then ground to obtain a slurry, and the slurry is coated on a conductive carbon paper to obtain the positive electrode; The molecular formula of the doped modified single crystal manganese-based lithium ion sieve is LiMn 2-x M x O4, 0<x≤0.1, M includes at least one of Al, Ni, Cr, and Cu; the doped and modified single crystal manganese-based lithium ion sieve is a spinel crystal; the preparation method of the doped and modified single crystal manganese-based lithium ion sieve specifically includes the following steps: (1) Mixing and dissolving a manganese salt, a surfactant and deionized water to obtain a solution A; dissolving an oxidant in deionized water to obtain a solution B; mixing solution A and solution B and transferring them to a hydrothermal reactor for a hydrothermal reaction, washing and drying the hydrothermal reaction product to obtain β-MnO2; the manganese salt is manganese sulfate monohydrate, the surfactant is polyvinyl pyrrolidone, and the oxidant is sodium chlorate; (2) The β-MnO2, lithium salt and metal compound are mixed in proportion and then calcined to obtain LiMn 2-x M x O4; the metal compound is a mixture of one or more of aluminum salt, nickel salt, chromium salt and copper salt.

2. The use according to claim 1, characterized in that: In step (1), the molar ratio of the manganese salt, the surfactant and the oxidant is (0.4-0.6):(0.5-0.6):

1.

3. The use according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 140-180° C., and the reaction time is 8-12 h.

4. The use according to claim 1, characterized in that: In step (1), the drying temperature is 50-70°C and the drying time is 10-14h.

5. The use according to claim 1, characterized in that: In step (2), the calcination temperature is increased at a rate of 2-4°C / min to 700-900°C, kept at that temperature for 10-12h, and then cooled at a rate of 2-4°C / min.

6. The use according to claim 1, characterized in that: In step (2), the lithium salt is one of lithium hydroxide, lithium carbonate and lithium nitrate; the aluminum salt is aluminum nitrate; the nickel salt is nickel nitrate; the chromium salt is chromium nitrate; and the copper salt is copper nitrate.

Citation Information

Patent Citations

  • Method for regulating and controlling stability of lithium ion sieve by cation doping

    CN103991908A